Tinjauan Undang-Undang Nomor 26 Tahun 2000 Tentang Pengadilan Hak Asasi Manusia terhadap Pertanggungjawaban Pidana Prajurit Tentara Nasional Indonesia Atas Kejahatan terhadap Kemanusiaan - Ephivanus Markus Nale Rimo; Maria Sisilia Lou Kelen (Pusat Riset dan Inovasi Nasional, 2025)
The role of the TNI is very important in creating and maintaining the security of the community in fulfilling human rights, but based on the long history in Indonesia, it is suspected that there has been violence and serious human rights crimes committed by state apparatus and security actors. The principle of command responsibility for military commanders, police superiors and other civilian superiors is at least three reasons that underlie the thinking of military commanders, police superiors and other civilian superiors, namely the commander or superior who has the power to give orders and is responsible for the failure to control or control his subordinates. This research examines the following issues: 1) How is criminal responsibility for crimes against humanity committed by TNI soldiers or troops in security restoration operations after the occurrence of military operations other than war (OMSP); 2) Which court is authorized to try the case of crimes against humanity committed by TNI soldiers or troops in security restoration operations after the occurrence of military operations other than war (OMSP). This type of research is normative legal research using the approach method used, namely the statutory approach and concept approach. Source of legal material. The sources of legal materials used are primary legal materials and secondary legal materials. Legal material search techniques are carried out by literature study or document study.